Mobile Health (mHealth) Applications: Transforming Preventive Health and Patient Engagement - Aung Myint; Nandar Hlaing; Zaw Min Oo; Rustiyana Rustiyana (Yayasan Adra Karima Hubbi, 2025)
The rapid expansion of mobile health (mHealth) applications has reshaped contemporary healthcare by enabling continuous preventive health management and enhancing patient engagement beyond traditional clinical settings. This study aims to examine how mHealth applications contribute to preventive health behaviors and patient engagement, with particular attention to usage patterns, behavioral outcomes, and contextual influences. A mixed-methods research design was employed, combining quantitative analysis of user surveys and application usage data with qualitative insights from interviews and a community-based case study. The findings reveal that frequent and sustained use of mHealth applications is associated with improved preventive behaviors, including increased physical activity, better dietary adherence, and enhanced medication compliance. The results also show that mHealth applications strengthen patient engagement by fostering greater health awareness, self-efficacy, and interaction with healthcare providers. However, variations in outcomes are influenced by digital literacy, personalization features, and the level of contextual support available to users. The study concludes that mHealth applications function as effective tools for transforming preventive health and patient engagement, but their impact depends on user-centered design and integration within broader health systems. The novelty of this research lies in its integrated analysis of preventive health outcomes and patient engagement within a single empirical framework, highlighting mHealth as a foundational component of modern, participatory preventive healthcare.